2021
DOI: 10.1097/scs.0000000000008375
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Youtube Videos on Botox Treatment of Gummy Smile

Abstract: In 1983 Hashimoto 6 classified IPEH into (1) pure, deriving from dilatation of the vessels of the head-neck region; (2) mixed, deriving from previous vascular lesions such as aneurysms, arteriovascular malformations, and chronic venous pathologies; (3) extravascular, originating from a hematoma caused by previous trauma. The present case, like the other 4 described in the literature, seems to belong to the first type. Intravascular papillary endothelial hyperplasia is more frequently found in the skin and subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Of indications, it was determined that information about the possible complications, contraindications, and cost of the procedure was quite limited. [20][21][22][23] It is known that information obtained by patients on the internet is very effective in the decisionmaking process regarding the treatment processes presented to them. 8,10,18 It was seen that very few of the videos conveyed information about dental sedation comprehensively and sensitively (9.43%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of indications, it was determined that information about the possible complications, contraindications, and cost of the procedure was quite limited. [20][21][22][23] It is known that information obtained by patients on the internet is very effective in the decisionmaking process regarding the treatment processes presented to them. 8,10,18 It was seen that very few of the videos conveyed information about dental sedation comprehensively and sensitively (9.43%).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies evaluating online platforms related to dental treatments and oral health have been published. 7,9,14,15,20,22,25,27,28 In the study of Heggie et al 21 in which mostly dental professionals evaluated websites, they stated that less than 3% of the web pages fully met the criteria, and the quality of the available internet information about dental intravenous sedation was insufficient. In our study, we encountered similarly unbalanced content in the parameters (e.g indication, advantage, risk) we used to measure video quality.…”
Section: Discussionmentioning
confidence: 99%
“…[5,7] However, studies have shown that the content of YouTube videos about health is not high in terms of scientific quality and reliability. [9][10][11] The current study evaluated the quality, credibility, and engagement of YouTube videos about cancer and nutrition. The mean mDISCERN score was 1.96±1.13 (poor quality), JAMA score was 1.65±1.89 (fair-poor quality), GQS score was 2.25±0.95 (fair quality).…”
Section: Discussionmentioning
confidence: 99%
“…Patients often lack knowledge and awareness regarding Botox applications in gummy smile; thus, the clinician should discuss all treatment options and their outcomes with the patient [ 21 ]. To determine the most favorable treatment approach, previous studies have suggested the classification of gummy smiles based on their etiopathogenic factors.…”
Section: Reviewmentioning
confidence: 99%